Identification of molecular crystals capable of undergoing an acyl-transfer reaction based on intermolecular interactions in the crystal lattice - Tamboli, Majid I.; Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Chemistry-A European Journal, 2013)
Investigation of the intermolecular acyl-transfer reactivity in molecular crystals of myo-inositol orthoester derivatives and its correlation with crystal structures enabled us to identify the essential parameters to support efficient acyl-transfer reactions in crystals: 1)the favorable geometry of the nucleophile (OH) and the electrophile (CO) and 2)the molecular assembly, reinforced by CH interactions, which supports a domino-type reaction in crystals. These parameters were used to identify another reactive crystal through a data-mining study of the Cambridge Structural Database. A 2:1 co-crystal of 2,3-naphthalene diol and its di-p-methylbenzoate was selected as a potentially reactive crystal and its reactivity was tested by heating the co-crystals in the presence of solid sodium carbonate. A facile intermolecular p-toluoyl group transfer was observed as predicted. The successful identification of reactive crystals opens up a new method for the detection of molecular crystals capable of exhibiting acyl-transfer reactivity.
Keywords: Acylation; domino reactions; intermolecular interactions; solid-state reactions; X-ray diffraction

Intramolecular cyclization of carbonate and thiocarbonate derivatives of myo-inositol in the solid state: implications for acyl group transfer reactions in molecular crystals - Tamboli, Majid I.; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Krishnaswamy, Shobhana (Chemistry-A European Journal, 2015)
Racemic 4-O-phenoxycarbonyl and 4-O-phenoxythiocarbonyl derivatives of myo-inositol orthoformate undergo thermal intramolecular cyclization in the solid state to yield the corresponding 4,6-bridged carbonates and thiocarbonates, respectively. The thermal cyclization also occurs in the solution and molten states, but less efficiently, suggesting that these cyclization reactions are aided by molecular pre-organization, although not strictly topochemically controlled. Crystal structures of two carbonates and a thiocarbonate clearly revealed that the relative orientation of the electrophile and the nucleophile in the crystal lattice facilitates the intramolecular cyclization reaction and forbids the intermolecular reaction. The correlation observed between the chemical reactivity and the non-covalent interactions in the crystal of the reactants provides a way to estimate the chemical stability of analogous molecules in the solid state.
Keywords: crystal engineering; cyclitols; inositols; nucleophilic substitution; solid-phase synthesis